INTELLECTUAL FIELD OF HISTORY - Andrey L. Andreev (Moscow Polytechnic University, 2022)
The paper focuses on the topical problems of teaching history and the standards of historical education in higher school and ponders over the role of historical component in training specialist of different spheres. These problems are treated through the prism of formation of creative intellectual environments.